1991
DOI: 10.1038/clpt.1991.82
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine as a metabolic probe: Validation of its use for acetylator phenotyping

Abstract: The use of two caffeine metabolite ratios for acetylator phenotyping was validated by demonstrating concordance with two sulfamethazine tests in 178 unrelated healthy subjects. The caffeine metabolites used for this purpose were 5-acetylamino-6-amino-3-methyluracil (AAMU), 1-methylxanthine (1X), and 1-methylurate (1U). The ratio AAMU/(AAMU + 1X + 1U), referred to as molar ratio or N-acetyltransferase, was compared with the ratio AAMU/1X. The results indicated that, for screening purposes, the acetylator phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1
9

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 0 publications
7
47
1
9
Order By: Relevance
“…value 0.55 reported by Tang et al [9]. The MRs measured by caffeine differed by collection period (spot, overnight) possibly due to alteration in clearance created by changes in organ blood flow following changes in posture.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…value 0.55 reported by Tang et al [9]. The MRs measured by caffeine differed by collection period (spot, overnight) possibly due to alteration in clearance created by changes in organ blood flow following changes in posture.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally the formation of 1MU which is further metabolised by xanthine oxidase may be significant. Tang et al [9] observed that the products of xanthine oxidase may be ignored if the observed MR is not within 10% of the antimode in young healthy individuals; within the 10% level, fast acetylators may be misclassified as slow. Thus, MRs calculated without measuring AAMU [12,171 or without accounting for the products of xanthine oxidase activity [16] may be misleading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est une substance ubiquitaire et relativement non toxique même à fortes doses, métabolisée par la voie de la N-acétylation et recommandée comme marqueur pour la détermination du phé-notype d'acétylation par plusieurs auteurs [26][27][28][29][30][31]. Le métabo-lisme de la caféine a été étudié in vivo et in vitro chez l'Homme et plus d'une dizaine de métabolites urinaires ont été déter-minés par CLHP [31][32][33].…”
Section: Introductionunclassified
“…Details of the phenotyping protocol and the bioanalytical method of the caffeine metabolites including its actual performance data (accuracy and precision) in the measurement of samples derived from this study have been recently reported by Jetter et al 41 In brief, NAT2 activity was determined by calculating urinary molar metabolic ratios of (AFMU þ AAMU)/(AFMU þ AAMU þ 1X þ 1U). 42 Metabolic ratios below 0.21 were defined as acceptance criterion to conclude an SA phenotype, whereas ratios X0.32 were required to conclude an RA phenotype. Subjects with intermediate ratios between these categories were considered not unequivocally classifiable and did not qualify for inclusion into the study.…”
Section: Subjects and Study Designmentioning
confidence: 99%